Evaluación de plataformas e-learning para la implantación de un campus virtual en la Universidad Técnica De Cotopaxi - Chariguaman Chanatasig, Marco Vinicio (2007)
Since its origins, The Distance Education has had changes to the developments in the Comunication, Information Technology, this one has made that there are many terms to designate to the distance training, the most used actully is E-Learning. Since twenty five years ego some Technologies has been base of the progress of E-Learning dissapearing the obstacle in the Teach-Learning process to distance and giving the posibility to be better the efects respect to the Presencial Education, between this Technologies there are: The Multimedia, Internet two, and the initiative of standarzation of educative components used by the LMS. This type of society stimulate a great demand of training and Education it make us some cuestions like these: what factors focus to the education? What chances we wait in the learning-teaching process at schools, universities and the continua training, in conclusión: what and when will we teach in the future?.